Ecological and economic effects of the landing obligation evaluated using a quantitative ecosystem approach: a Mediterranean case study. (25th June 2018) - Celić, Igor; Libralato, Simone; Scarcella, Giuseppe; Raicevich, Saša; Marčeta, Bojan; Solidoro, Cosimo
Abstract: The reformed Common Fisheries Policy [Regulation (EU) 1380/2013] introduces the obligation to land unwanted catches gradually from 2015 to 2019 with the aim to reduce discards. The ecological and economic consequences of this controversial regulation are evaluated here using an ecosystem model for the North-Eastern Adriatic Sea to quantify the long-term stocks' biomass, landings, and fisheries revenues under future scenarios with and without landing obligation. Results indicate that landings will increase by +13%, causing an increase in fishermen workload, reduction of biomasses at sea (∼−0.20%) for species of both commercial and non-commercial interest, thus a small decrease in fisheries revenue (∼−0.50%). Selling landed unwanted catches for fishmeal production will not compensate the economic losses. Additional adaptation scenarios were tested: (i) introduction of quotas for small pelagics, (ii) reduction of effort for bottom trawlers, (iii) improvement of gear selectivity, and (iv) a combination of (i) and (iii). Improving selectivity and introducing quotas resulted the best alternative but none of the adaptation scenarios compensated the adverse effects of the landing obligation, suggesting that this management measure has ecological and economic negative effects in systems where fisheries are not regulated by quota such as the Mediterranean Sea.